LOKAKARYA PENGENALAN MAKANAN DAN JAJANAN YANG MENGANDUNG PEMANIS DAN PEWARNA BUATAN PADA SISWA SMP NEGERI 5 CIANJUR MELALUI DEMONSTRASI SEDERHANA - Andi Wahyudi; Riki Perdana; Endi Rochaendi; Yusinta Dwi Ariyani (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
It is very important to introduce good food and snacks to students. This is useful for maintaining the health of students when consuming snacks in the school canteen. This service aims to increase students' knowledge and attitudes towards types of food that contain artificial sweeteners and dyes through simple demonstration methods. The service method is a pretest and posttest experimental research using test instruments and questionnaires. The population in this study were students at SMPN 5 Cianjur, West Java. The sample was selected randomly so that 37 students were selected. Data analysis using comparative descriptive. The results of this study were (1) a simple demonstration method could increase students' knowledge of the type of food based on n.gain dye 0.75 (high) and sweetener n-gain 0.69 (medium); (2) students' attitudes about food coloring and sweeteners are at a good level. (3) The relationship between the aspects of attitude and knowledge in this service includes the domain of disciplinary attitude towards sweeteners (0.92) and 0.442 dyes, the creative domain for sweeteners 0.789 and dyes 0.416, the domain of responsibility for sweetener aspects 0.279 and dyes 0.407. The introduction of food snacks through effective methods increases students' knowledge of sweeteners and food coloring that are healthy.